2021
DOI: 10.3390/su13084092
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use and Land-Cover (LULC) Change Detection and the Implications for Coastal Water Resource Management in the Wami–Ruvu Basin, Tanzania

Abstract: Evaluation of river basins requires land-use and land-cover (LULC) change detection to determine hydrological and ecological conditions for sustainable use of their resources. This study assessed LULC changes over 28 years (1990–2018) in the Wami–Ruvu Basin, located in Tanzania, Africa. Six pairs of images acquired using Landsat 5 TM and 8 OLI sensors in 1990 and 2018, respectively, were mosaicked into a single composite image of the basin. A supervised classification using the Neural Network classifier and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…These overall findings agree with a larger LULC study of the WRB (Ngondo et al, 2021) and are related to water resource implications. Since 1990, coastal populations have increased significantly with related demands for agricultural products and water, resulting in the conversion of wetlands to cultivated lands.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These overall findings agree with a larger LULC study of the WRB (Ngondo et al, 2021) and are related to water resource implications. Since 1990, coastal populations have increased significantly with related demands for agricultural products and water, resulting in the conversion of wetlands to cultivated lands.…”
Section: Resultssupporting
confidence: 90%
“…Rainfall (900 to 1300 mm p/a; GLOWS-FIU, 2014a) occurs in March-May and October-December, FIU, 2014b;2014c). Upstream of the estuary, the Ruvu River flows through major agricultural, industrial, and urban areas where freshwater is diverted for irrigation, industrial, aquaculture and domestic use (Ngondo et al, 2021). With rapid coastal expansion, particularly at Dar es Salaam where there is a critical water supply/ demand deficit, the WRB is of high strategic importance and has been the subject of numerous impact assessments, predictive models, policy documents and published research (e.g., GLOWS-FIU, 2014ad;van Eeden et al, 2016;Mdee, 2017;Alphayo and Sharma, 2018;Miraji et al, 2019;Ngondo et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the study reported by [139] showed that LULC changes are one of the key drivers of hydrological changes in the watershed. LULC change is a complex source of pressure that threatens the sustainability and management of water resources [136,140]. The impact of the LULC change pattern on the sub-basins connecting coastal areas and highland areas has led to economic, social, political, and environmental problems at the national, regional, and local levels in many countries.…”
Section: Lulc Change Implications For Water Resources Managementmentioning
confidence: 99%
“…Furthermore, the estuary provides nutrients that nourish adjacent coastal marine ecosystems and nurseries (Hoguane and Armando, 2015) and the dense mangrove forests are an important carbon sink and mitigation against climate change (Amade et al, 2019). Remote sensing and GIS techniques are often applied to detect change in LU and LC by season or over longer time frames (Mallupattu and Reddy, 2013;Berlanga-Robles and Ruiz-Luna, 2002;Hudak and Wessman, 1998;Ngondo et al, 2021). Analysis of satellite images is a cost-effective means of mapping physiognomic habitats, including mangroves, wetlands, sand and seagrass beds and coastline morphology (Dittrich et al, 2020;Dymond et al, 2019;Marzialetti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%